2020
DOI: 10.1021/acsnano.9b08962
|View full text |Cite
|
Sign up to set email alerts
|

A Heterojunction Structured WO2.9-WSe2 Nanoradiosensitizer Increases Local Tumor Ablation and Checkpoint Blockade Immunotherapy upon Low Radiation Dose

Abstract: Radiotherapy (RT) in practical use often suffers from offtarget side effects and ineffectiveness against hypoxic tumor microenvironment (TME) as well as remote metastases. With regard to these problems, herein, we provide semiconductor heterojunction structured WO 2.9 -WSe 2 -PEG nanoparticles to realize a synergistic RT/photothermal therapy (PTT)/checkpoint blockade immunotherapy (CBT) for enhanced antitumor and antimetastatic effect. Based on the heterojunction structured nanoparticle with high Z element, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(94 citation statements)
references
References 60 publications
0
94
0
Order By: Relevance
“…Despite the favorable results, several studies have shown limited results for complete tumor remission for ICIs with hyperthermia. Thus, triple combination strategies including ICIs with radio-/chemotherapy or TLR agonists have been studied, and they have also achieved favorable results with decreased tumor volume, increased metastatic dissemination, prevention of tumor rechallenge, and improved overall survival (115)(116)(117)(118)(119)(120)(121)(122)(123)(124)(125)(126). A case report also found that hyperthermia and ipilimumab combined with IL-2 achieved complete clinical remission of stage IV triple-negative breast cancer with lung metastasis (127).…”
Section: Preclinical Data Combining Hyperthermia and Icismentioning
confidence: 99%
“…Despite the favorable results, several studies have shown limited results for complete tumor remission for ICIs with hyperthermia. Thus, triple combination strategies including ICIs with radio-/chemotherapy or TLR agonists have been studied, and they have also achieved favorable results with decreased tumor volume, increased metastatic dissemination, prevention of tumor rechallenge, and improved overall survival (115)(116)(117)(118)(119)(120)(121)(122)(123)(124)(125)(126). A case report also found that hyperthermia and ipilimumab combined with IL-2 achieved complete clinical remission of stage IV triple-negative breast cancer with lung metastasis (127).…”
Section: Preclinical Data Combining Hyperthermia and Icismentioning
confidence: 99%
“…Similarly, tungsten's high atomic number has also received interest. Dong et al [48] synthesized a WO 2.9 -WSe 2 nanoparticle system that can perform both PTT and radiosensitizer, resulting in ICD at a relatively lower temperature and dose as measured by an increase in calreticulin translocation in treated 4T1 cells in vitro. In in vivo models, combination radiotherapy and PTT mediated via these particles in addition to anti-PDL1 therapy also resulted in drastic decreases in primary tumor volume, as well as an increase in CD4+ and CD8+ T cells in the tumor microenvironment and immune memory effect, which inhibited tumor growth after a secondary inoculation (Figure 3b).…”
Section: Radiosensitizersmentioning
confidence: 99%
“…Magnetic hyperthermia (MHT) refers to the thermal treatment technology of magnetic nanoparticles on tumors under strong alternating magnetic field (AMF) [86] . Unlike the widely used photochemotherapy, MHT can treat deep‐seated cancer cells in various organs under its decent tissue penetration [87] …”
Section: Combination Of Nanotechnology‐based Immune Checkpoint Blockimentioning
confidence: 99%
“…[86] Unlike the widely used photochemotherapy, MHT can treat deep-seated cancer cells in various organs under its decent tissue penetration. [87] The MHT designed by Chao et al primarily based on FeNP and combines systemic anti-CTLA4 checkpoint antibodies and local immune adjuvants. They were demonstrated to be in multiple tumor models that the immune response of the vaccine system promoted by this MHT immunotherapy had powerful function of inhibiting tumor cell metastasis and prevented tumor recurrence.…”
Section: Magnetic Therapymentioning
confidence: 99%